Effect of addition of expanded graphite (EG) on the synthesis and characteristics of poly(ethylene terephthalate) modified with cyclohexanedimethanol (PETG) - Paszkiewicz, S; Szymczyk, A; Špitalský, Z; Mosnáček, J; Janus, E; Rosłaniec, Z (Polimery, 2013)
In this work, the effect of the addition of carbon nanofiller (expanded graphite) on the process of synthesis of PETG (PET-ran-PCT copolymer), morphology of the resulting nanocomposite and its phase transitions has been studied. The examined PETG contained 0.1 wt. % expanded graphite (EG) in the form of single graphene sheets and (predominantly) loosely assembled graphene bundles, as it was observed by SEM analysis (Fig. 4a). No influence of EG nanoparticles on the physical changes in the PET-ran-PCT copolymer was found. DSC thermograms of PETG with 20 or 30 mol. % PCT content did not show melting or crystallization peaks (Fig. 5). The results of quantitative analysis of by-products using gas chromatography indicated that the composition of the prepared polymer was in accordance with that calculated from the stoichiometric amounts of main components. Additionally, the molecular structure of synthesized copolymers was confirmed by 1H NMR spectroscopy (Fig. 3). The signals in the range 2,41—1,63 ppm (peak d) indicated the presence of cis-trans isomers corresponding to cyclohexanedimethanol in the copolymer.